The Face of Russia, Part 3: Facing the Future - Grigor, Murray (United States, 1998)
The Face of Russia is a personal interpretation of Russia’s cultural history by one of America’s pre-eminent Russian scholars, James H. Billington. Part 3: Old Russia considered instrumental music to be the work of the devil; and no musical instruments were permitted in Russian Orthodox churches. The imperial court played Italian-style music; but only in the late nineteenth century, coinciding with the rise of the Russian revolutionary movement, did Russian music suddenly explode through the efforts of talented, unconventional composers. In this episode, viewers meet Musorgsky, the genius of this group, who dramatized in his operatic masterpiece, Boris Godunov, the conflict between Russia’s rulers and its people, its reverence for tradition and its passion for revolution. The program then introduces Sergei Eisenstein, the film director and brilliant innovator, who united all forms of Russian art into the new icon of film. His revolutionary cinema of the early Soviet period retold history with such power that the images became more real than the events—challenging today’s filmmakers to use the cinema to continue reshaping the face of Russia. Finally, the program examines how Russia’s traditional and new art forms are influencing the country’s current political process and its emerging democracy.
Keywords: Documentary films